LETRAMENTO CRÍTICO E VOZES DE ALUNAS E PROFESSORA ACERCA DAS IDENTIDADES SOCIAIS DE GÊNERO COM INTERSECÇÃO DE RAÇA E DE CLASSE NO LIVRO DIDÁTICO DE LÍNGUA INGLESA - Clara, Michele Padilha Santa (2017)
This research was carried out in a public school in the city of Ponta Grossa/PR, it specifically involves ten students of the third grade of secondary school in the technical course for Teacher Training, and their English Language teacher. This study aims to analyze how the English Language textbooks represent gender social identities on race and class, and to identify what the teachers and students’ views are on these identities. Thus, I intend to respond the following survey inquiries: How gender social identities with race and class intersections are represented by the English Language textbook Way to Go 1? What are the teachers and students’ views on social identities with race and class intersections? As to the theoretical contribution that supports this research, we turn to Hall (1990, 2006), Moita Lopes (1994, 2002) and Block (2007, 2014), who run on about identities. For the understanding of the matters regarding literacy, I look to Street (2001, 2006, 2014), to Crenshaw (1991, 2004) concerning intersectionality, and to Ferreira (2014) concerning the textbook. This research regards qualitative Applied Linguistics,documentary and an ethnographic case study. In order to collect data,questionnaires, autobiographic narratives, interviews, and logs were held. The results indicate a low representation of gender identities with race and class intersections in the textbook Way to Go 1. In addition, among the few black-woman images that show up in the book, most of them are degrading or stereotyped. In addition, it was possible to see that while some of the participants in this research had suffered from racial prejudice or racism, others had already witnessed someone suffering from it. Therefore, I conclude that racial prejudice is still present in many sectors of society, such as schools, textbooks, families, media and others. However, even when it happens, the teacher has the possibility to promote critical literacy in class, making their students recognize and question the ideologies imposed by the dominating society, disrupting certain identities.